Case Report: A Novel EIF2B3 Pathogenic Variant in Central Nervous System Hypomyelination/Vanishing White Matter - Wongkittichote, Parith; Mar, Soe Soe; McKinstry, Robert C.; Nguyen, Hoanh (Frontiers in Genetics, 2022)
Leukodystrophies are a group of heterogeneous disorders affecting brain myelin. Among those, childhood ataxia with central nervous system hypomyelination/vanishing white matter (CACH/VWM) is one of the more common inherited leukodystrophies. Pathogenic variants in one of the genes encoding five subunits of EIF2B are associated with CACH/VWM. Here we presented a case of CACH/VWM who developed ataxia following minor head injury. Brain magnetic resonance imaging showed extensive white matter signal abnormality. Diagnosis of CACH/VWM was confirmed by the presence of compound heterozygous variants in EIF2B3: previously known pathogenic variant c c.260C>T (p.Ala87Val) and novel variant c.673C>T (p.Arg225Trp). Based on American College of Medical Genetics (ACMG) recommendations, we classified p.Arg225Trp as likely pathogenic. We report a novel variant in a patient with CACH/VWM and highlight the importance of genetic testing in the patients with leukodystrophies.